141k views
4 votes
5x - 4y = 1
2x + 3y = 5

User Adam Young
by
6.5k points

1 Answer

3 votes

Answer:

x = 1 and y = 1.

Explanation:

Given equations are :
5x - 4y = 1 ...... (1) and\\2x + 3y = 5 .......(2)

Now using equation (1)


5x - 4y = 1


5x = 4y + 1


x = (4y + 1)/(5)

By substituting the value of x in equation 2


2x + 3y = 5


2((4y + 1)/(5)) + 3y = 5

Further solving


(8y+ 2)/(5) + 3y = 5


8y + 2 + 15y = 25


23y = 25 - 2 = 23


y = 23/23 = 1

Now substituting the value of y in x,


x = (4y + 1)/(5)


x = (4 (1) + 1)/(5) = (5)/(5) = 1

User Brian Christensen
by
5.8k points